Transport processes of the legume symbiosome membrane - Clarke, Victoria C.; Loughlin, Patrick C.; Day, David A.; Smith, Penelope M. C. (Frontiers in plant science, 2014)
The symbiosome membrane (SM) is a physical barrier between the host plant and nitrogen-fixing bacteria in the legume:rhizobia symbiosis, and represents a regulated interface for the movement of solutes between the symbionts that is under plant control. The primary nutrient exchange across the SM is the transport of a carbon energy source from plant to bacteroid in exchange for fixed nitrogen. At a biochemical level two channels have been implicated in movement of fixed nitrogen across the SM and a uniporter that transports monovalent dicarboxylate ions has been characterized that would transport fixed carbon. The aquaporin NOD26 may provide a channel for ammonia, but the genes encoding the other transporters have not been identified. Transport of several other solutes, including calcium and potassium, have been demonstrated in isolated symbiosomes, and genes encoding transport systems for the movement of iron, nitrate, sulfate, and zinc in nodules have been identified. However, definitively matching transport activities with these genes has proved difficult and many further transport processes are expected on the SM to facilitate the movement of nutrients between the symbionts. Recently, work detailing the SM proteome in soybean has been completed, contributing significantly to the database of known SM proteins. This represents a valuable resource for the identification of transporter protein candidates, some of which may correspond to transport processes previously described, or to novel transport systems in the symbiosis. Putative transporters identified from the proteome include homologs of transporters of sulfate, calcium, peptides, and various metal ions. Here we review current knowledge of transport processes of the SM and discuss the requirements for additional transport routes of other nutrients exchanged in the symbiosis, with a focus on transport systems identified through the soybean SM proteome.